Issuer's Responsibility in Bond Default Disputes - Annisa Larasati; M. Rivky Abdillah Putra; Fatimah Panggabean; Andhika Bayu Pranata; Syifa Sirait (ISNU Nine-Star Multidisciplinary Journal, 2025)
Bonds as one of the capital market instruments are a long-term funding option for issuers. However, in practice, it is not uncommon for defaults to arise in legal disputes between issuers and investors. This study aims to analyze the form of legal responsibility of issuers in the case of bond default and review the dispute resolution mechanisms available in Indonesia. The research method used is normative juridical with a legislative approach, court decisions, and case studies. The results of the study show that issuers have a civil legal responsibility to fulfill the obligation to pay interest and principal bonds as stated in the bond issuance agreement. The failure of the issuer to fulfill these obligations may lead to lawsuits from bondholders, either through the courts or dispute resolution institutions such as arbitration and mediation. In addition, the role of the Financial Services Authority (OJK) is very important in supervising and protecting investors. This study recommends strengthening regulations and information transparency from issuers to prevent future defaults.